Fundamentals Of Moral Islamic Education (Analysis Of Surat Al-Araf Verse 199) - Triyani Oktofiyah (Penerbit Hellow Pustaka, 2023)
Abstract. The study of moral education is a very urgent and important discussion in the world of education. This discussion has been widely studied by researchers, thinkers and also writers of other scientific works. This study uses a qualitative research method that originates from the Qur'an and its interpretations, then analyzes its contents to obtain conclusions. This study focuses on Q.S.Al-Araf. This paper finds out how the concept of the basics of moral education is in the perspective of the Koran. In the view of the Qur'an, moral education must be educated to humans, so that they can have morals towards Allah SWT, towards themselves, towards their families, and towards the surrounding community.